The combined effects of coping and pain interference on army readiness - Kegel, Jessica L.; Kazman, Josh B.; Clifton, Daniel R.; Emanuele, Peter; Nelson, D. Alan; Deuster, Patricia A. (Frontiers in Pain Research, 2023)
Chronic pain and associated interference with daily activities are common in the military and impact Force readiness. Chronic pain affects one-third of service members and is a leading cause of medical non-readiness (MNR) in the military. Research suggests that underlying psychological mechanisms related to trait coping styles and pain interference (PI) affect functional outcomes, but little research exists examining this relationship within an Army population. The purpose of this study was to examine the combined effects of PI and coping on U.S. Army soldier readiness by using annual well-being data from the Global Assessment Tool (GAT) and medical non-readiness (MNR) based on duty restriction records. The sample comprised 866,379 soldiers who completed the GAT between 2014 and 2017 with no duty restrictions at the time of baseline GAT completion; subjects were observed through 2018 for duty restrictions. Parametric survival regression models with a Weibull distribution predicted demographic-adjusted hazards of MNR by dichotomized PI (no PI/PI) and beneficial/non-beneficial use of GAT coping components (good coping, bad coping, catastrophizing-flexibility, and catastrophizing-hopelessness). Incident MNR was evaluated for all duty restrictions, and stratified by selected body systems (upper extremity, lower extremity, psychiatric). Among soldiers with PI, hazards were higher in those reporting non-beneficial coping styles (bad coping, hopelessness) and lower in those reporting beneficial coping styles (good coping, flexibility). Across all coping styles, PI/coping interactions were particularly strong for catastrophizing-hopelessness and when examining MNR from psychiatric conditions. These findings suggest some synergistic associations between pain and coping that may impact pain-related occupational disability. Coping skills may be an effective interventional target for chronic pain reduction/prevention within military programs, such as the Master Resilience Training Course offered to soldiers in the Army. Further research should assess whether early coping style interventions can reduce pain-related outcomes.